Myths, Wishful Thinking, and Accountability in Predator Conservation and Management in the United States - Blossey, Bernd; Hare, Darragh (Frontiers in Conservation Science, 2022)
Large predators are thought of as ecological keystone species, posterchildren of conservation campaigns, and sought-after targets of tourists and photographers. At the same time, predators kill livestock and huntable animals, and occasionally people, triggering fears and antipathy among those living alongside them. Until the 1960's government-sponsored eradication and persecution campaigns in the United States prioritized interests of livestock producers and recreational hunters, leading to eradication of wolves and bears over much of their range. Without large predators, subsidized by changes in agricultural practices and milder winters, ungulate populations erupted, triggering negative ecological impacts, economic damage, and human health crises (such as tick-borne diseases). Shifting societal preferences have ushered in more predator-friendly, but controversial wildlife policies, from passively allowing range expansion to purposeful reintroductions (such as release of wolves in Yellowstone National Park). Attempts to restore wolves or mountain lions in the U.S. and protecting coyotes appear to enjoy strong public support, but many state wildlife agencies charged with managing wildlife, and recreational hunters continue to oppose such efforts, because they perceive predators as competitors for huntable animals. There may be compelling reasons for restoring predators or allowing them to recolonize their former ranges. But if range expansion or intentional releases of large predators do not result in ecosystem recovery, reduced deer populations, or Lyme disease reductions, conservationists who have put their reputation on the line and assured decision makers and the public of the important functional role of large predators may lose public standing and trust. Exaggerated predictions by ranchers and recreational hunters of greatly reduced ungulate populations and rampant livestock killing by large carnivores may lead to poaching and illegal killing threatening recovery of predator populations. How the return of large carnivores may affect vegetation and successional change, ungulate population size, other biota, livestock and human attitudes in different landscapes has not been appropriately assessed. Societal support and acceptance of living alongside predators as they expand their range and increase in abundance requires development and monitoring of social, ecological and economic indicators to assess how return of large predators affects human and animal and plant livelihoods.